“THE ROLE OF MIRZO ULUGBEK IN WORLD CIVILIZATION” (Multidisciplinary Journal of Science and Technology, 2026)
This article highlights the important aspects of Mirzo Ulugbek’s life and socio-political activities. Also, the role of his rich scientific heritage in the development of world culture and science is discussed in a comprehensive manner. In particular, the content and significance of the work “Ziji Sultaniy” is described. The article reveals the short-term activity of Mirzo Ulugbek as both a ruler and a great scientist through various historical evidence and examples. In addition, the respect and interest in his legacy in the world scientific community is also deeply analyzed.